2020
DOI: 10.3390/en13123171
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Control Methods for PV-Integrated Shading Devices

Abstract: This study aimed to develop a building-integrated photovoltaic (BIPV) device and optimal control methods that increase the photovoltaic (PV) efficiency and visual comfort of the indoor space. A louver-type PV-integrated shading device was suggested and an artificial neural networks (ANN) model was developed to predict PV electricity output, work plane illuminance, and daylight glare index (DGI). The slat tilt angle of the shading device was controlled to maximize PV electricity output based on three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Standard parameters studied include the width of the louvers [22], the optimal inclination of the louvers [23], and the reflectance and transmittance of the louver material [24]. In terms of evaluation indexes, the energy consumption index, and energy saving rate; in terms of the thermal comfort index: PMV [25,26], temperature, and cumulative solar radiation [25,27]; and in terms of the light comfort indexes: daylight glare index (DGI) [28,29], daylight glare probability (DGP) [30,31], useful daylight illuminance (UDI) [32,33], and daylight factor (DF) [34][35][36] are often used in the study. In addition, several studies propose optimal control schemes for louver shading in different climate zones, orientations, and periods [31,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Standard parameters studied include the width of the louvers [22], the optimal inclination of the louvers [23], and the reflectance and transmittance of the louver material [24]. In terms of evaluation indexes, the energy consumption index, and energy saving rate; in terms of the thermal comfort index: PMV [25,26], temperature, and cumulative solar radiation [25,27]; and in terms of the light comfort indexes: daylight glare index (DGI) [28,29], daylight glare probability (DGP) [30,31], useful daylight illuminance (UDI) [32,33], and daylight factor (DF) [34][35][36] are often used in the study. In addition, several studies propose optimal control schemes for louver shading in different climate zones, orientations, and periods [31,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…It is more prominent in solar experiments since researchers can postulate solar panels' performance and durability using computational tools in either simulation or practical experiments. During our screening, we found that some authors performed their studies practically in real time [35] , [36] , [58] , and many authors adopted simulation tools with curated data sets to obtain their findings [5] , [67] , [4] . In another situation, simulation and practical approaches have been applied in the same experiments for a better comparative analysis [50] , [61] , [41] .…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 reveals that ANN wins in terms of best performing ML methods [38] , [32] , [50] , [54] , [58] , [61] . Jung et al [54] achieved 97% score in their testing dataset using ANN, whereas Kim and Kim [36] achieved 96.42% and Zhao et al [50] achieved 82.90% score.…”
Section: Resultsmentioning
confidence: 99%
“…In Korea, at a latitude very close to that of Athens, it has been noticed that simple geometry shading systems do not differ in efficiency compared with standard photovoltaic roof solutions [18]. The research in [68] proposes a BIPV device and optimal control method that increases the PV efficiency, maintaining visual comfort. The analysis was performed on a small-scale prototype of a PV louvre.…”
Section: Energy Performance: Pv Generation and Savingsmentioning
confidence: 99%